Inovação, desenvolvimento de produtos e a experiência do usuário: estudo de caso em uma empresa de equipamentos médicos - Laís de Aguiar Oribe (2019)
Innovation is acknowledged to be an important strategy to highlight the company in the market, however, only the act of transforming ideas and innovating in processes and products, does not guarantee the success with users and the return on investments. The users have the important role of validating these innovations, whether they are incremental or disruptive, making them market differentials for the company. This present work shows a study about how to align the innovation strategies adopted by the medical equipment company to the user demands from user-centered product development. This investigation was based on the analysis of product engineers experience about the main innovative practices adopted for the multiparametric monitors by GE Healthcare (GEHC), Contagem facility, Minas Gerais and the experiences of these monitors users on Hospital Público Regional de Betim (HPRB). For this, a qualitative research method was used from concepts of Grounded Theory and the Course of Action in which it was conducted interviews with the company's product engineers and performed observation of the work and interviews with medical equipment users in the hospital. The contributions of this research aim to support the company's innovative practices more properly and encourage them to seek in the users' experiences the necessary learning for the development of medical products. From the users point of view, the possibility of perceiving from the practice, demands that currently are not met and that could favor their work routine in the patients care. The results of this work lead to the conclusion that there is a connection between the innovations made by the company and the users demands and this relationship can be improved through the best investment in user-centered development, use of technological innovation to develop new applications for more affordable technologies and increased agility in the development process.